From the Forest to the Dish: A Comprehensive Study of the Wildmeat Value Chain in Yangambi, Democratic Republic of Congo - Van Vliet, Nathalie; Muhindo, Jonas; Nyumu, Jonas Kambale; Nasi, Robert (Frontiers in Ecology and Evolution, 2019)
Given the importance of wildmeat for local and national economies, understanding the structure and operations of the informal wildmeat value chains is necessary to provide recommendations for a sustainable wildmeat sector. However, the limited number of case studies available hinders our capacity to tailor such recommendations to different contexts. In this study, we use a value chain approach to explore the structure and functioning of the trade. We identify the main barriers to entry into the business and the main levers that can be used to reverse unsustainable value chains in the Yangambi landscape, Democratic Republic of Congo. Bushmeat remains the most consumed source of meat both in the main urban area and in surrounding villages. Urban consumption generates a trade of about 103–145 tons of bushmeat per year for a human population of 37,997 inhabitants. Yangambi combines all the factors for a depletion scenario: a quasi-open access system and high levels of dependency on the resource at all levels of the chain (from consumers to hunters). Despite this, emblematic species such as the chimpanzee, buffalo, okapi, red colobus and giant pangolin are still present in the area. The trade chain follows a ‘redundant’ structure with few barriers to participation in the sector: (1) many hunters and rights holders; (2) many traders; (3) significant demand. Hunters, on average, obtain a higher profit than traders, who bear the highest costs of transportation, fines and bribes. Reducing unsustainable trade in this context, will necessarily imply reducing the burden on natural ecosystems as the main providers of animal protein. In contrast, supporting processes to re-structure local governance systems in this post-conflict context will also support of efforts to reverse unsustainable use. Our study illustrates that no two bushmeat market chains are alike. Recommendations to reduce unsustainable trade in urban areas need to be tailored to specific contexts, taking into consideration differences in terms of whether markets are open or underground, the length of the trade chains, the existence and type of barriers to entry, the number and type of stakeholders involved and the factors influencing the demand–supply equilibrium.